Effect of whitening and desensitizing dentifrices on composite surfaces treated with surface sealants - Santos, Paulo Henrique dos [UNESP]; Brogin, Fabiana Ferres; Catelan, Anderson; Suzuki, Thaís Yumi Umeda; Guedes, Ana Paula Albuquerque; Pavan, Sabrina; Assunção, Wirley Gonçalves [UNESP]; Briso, André Luiz Fraga [UNESP] (Wiley-Blackwell, 2013)
This study evaluated the effect of different dentifrices on the microhardness and surface roughness of composite surfaces covered by surface sealants. Samples of Filtek P60 were made and divided into groups, in accordance with surface treatments: G1 - Fortify; G2 - Fortify Plus; G3 - control (none). For Knoop microhardness evaluation, the specimens were placed in a microdurometer, under a load of 50 g for 15 sec. The analyses of surface roughness were carried out individually in a profilometer. The specimens were submitted to toothbrushing using dentifrices: Colgate Maximum Protection Anti-caries, Colgate Whitening or Sensodyne, diluted in distilled water (1:3) for 30 000 cycles. The results showed that the control group (G3) presented the highest microhardness values. The control group presented, before toothbrushing, the lowest surface roughness values, and after toothbrushing there were no differences among the experimental groups. The maintenance of the lowest values of microhardness demonstrated the effectiveness of these sealant materials to support the abrasive wear.